Strategies for providing healthcare services to street-dwellers in Dhaka city: Evidence from an operations research - Uddin Jasim; Koehlmoos Tracey P; Saha Nirod C; Islam Ziaul; Khan Iqbal A; Quaiyum MA (BMC, 2012)
Abstract Background In almost every major urban city, thousands of people live in overcrowded slums, streets, or other public places without any health services. Bangladesh has experienced one of the highest rates of urban population growth in the last three decades compared to the national population growth rate. The numbers of the urban poor and street-dwellers are likely to increase at least in proportion to the overall population growth of the country. The street-dwellers in Bangladesh are extremely vulnerable in terms of their health needs and healthcare-seeking behaviours. In Bangladesh, there is no health service-delivery mechanism targeting this marginalized group of people. This study, therefore, assessed the effectiveness of two models to provide primary healthcare (PHC) services to street-dwellers. Methods This study of experimental pre-post design tested two models, such as static clinic and satellite clinics, for providing PHC services to street-dwellers in the evening through paramedics in Dhaka city during May 2009-April 2010. Both quantitative and qualitative techniques were used for collecting data. Data were analyzed comparing before and after the implementation of the clinics for the assessment of selected health and family-planning indicators using the statistical t-test. Services received from the model l and model 2 clinics were also compared by calculating the absolute difference to determine the relative effectiveness of one model over another. Results The use of healthcare services by the street-dwellers increased at endline compared to baseline in both the model clinic areas, and the difference was highly significant (p < 0.001). Institutional delivery among the female street-dwellers increased at endline compared to baseline in both the clinic areas. The use of family-planning methods among females also significantly (p < 0.001) increased at endline compared to baseline in both the areas. Conclusions As the findings of the study showed the promise of this approach, the strategies could be implemented in all other cities of Bangladesh and in other countries which encounter similar problems.